DFT-based modeling of polypyrole/B12N12 nanocomposite for the photocatalytic applications. (November 2022) - Kaviani, Sadegh; Tayurskii, Dmitrii A.; Nedopekin, Oleg V.; Piyanzina, Irina
Abstract: Boron-based nanocomposites considered as one of the most promising photocatalysts, have drawn significant attention in the degradation of pollutants in aquatic environments. In this regard, density functional theory calculations were carried out on the B12 N12 nanocluster interacted with various lengths of (PPy)n oligomers (n = 3, 5, 7, and 9) to predict the optical, electronic, charge transfer properties as well as the optimum composition of obtained (PPy)n /B12 N12 nanocomposites. It was found that the most stable nanocomposite corresponds to (PPy)3 /B12 N12, which was supported by its greatest adsorption energy (−59.460 kcal mol −1 ) in the gas phase. The calculations in the gas phase and water showed that water as a solvent has a key role in the interaction between B12 N12 nanocluster and (PPy)n oligomers. The results revealed that the adsorption of (PPy)9 oligomer on the B12 N12 nanocluster leads to the highest reduction ( ∼ 2.672 eV) in the energy gap (Eg ) value, while the lowest reduction ( ∼ 1.475 eV) was related to (PPy)3 /B12 N12 nanocomposite. Moreover, the natural bond orbital analysis showed that the charge flows from (PPy)n oligomers to the B12 N12 nanocluster. Polarizability (α0 ) and first hyperpolarizability (β0 ) values revealed that the adsorption of (PPy)9 oligomer on the surface of B12 N12 nanocluster has the most considerable effect on the optical response of B12 N12 nanocluster due to increasing the α0 and β0 values about 492.49 and 5070.07 a.u, respectively. The UV–Vis spectra analysis showed that the (PPy)9 /B12 N12 nanocomposite has the highest bathochromic shift ( ∼ 245.39 nm) among other nanocomposites. Finally, quantum theory of atoms in molecules analysis showed that (PPy)n oligomers interact with B12 N12 nanocluster through the partial covalent interactions. Graphical abstract: Image 1 Highlights: DFT method was employed to development of novel (PPy)n /B12 N12 nanocomposites for photocatalytic applications. The photocatalytic activities of B12 N12 doped with polypyrole were improved. (PPy)9 -doped B12 N12 shows the most remarkable photocatalytic activities. (PPy)n /B12 N12 nanocomposites can be used in optoelectronic devices.